Accumation rates of manganese in a pelagic sediment core using 231Pa activity - Michael L Bender; Teh-Lung Ku; Wallace S Broecker (PANGAEA, 2022)
For a pelagic sediment core taken in the Atlantic Ocean, The decrease of unsupported 231Pa was used for the determination of the accretion rate. Because CaCO3 is a Mn-free diluent, the Mn concentration results and the sediment accumulation rate results are given on a carbonate-free basis. CaCO3 content ofcores raised from below the carbonate compensation level is taken as zero. The in situ density of water-free deep-sea cores was assumed to be 0.7 g/cm^3 , this could lead in some cases to an error.
In: Bender, ML et al. (2022): Accumulation rates of manganese in pelagic sediments and nodules [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.949670